“FAMILIAS E VEZINOS DEL COMERZIO”. THE MERCANTILE COMMUNITY IN LA VILLA DE ALBACETE, FORMS OF ECONOMIC ORGANIZATION AND SOCIAL REPRODUCTION AT THE END OF THE OLD REGIME - Gómez Carrasco, Cosme (Revista de Historia Social y de las Mentalidades, 2011)
At the end of the Old Regime in the town of Albacet e a social group connected to  the commercial activities consolidated. A  merchant community that was developed in tie to  the agrarian activities. The position of this town  in a crossroad between the capital of Spain  and the Mediterranean periphery favored the economi c growth of these families. The  objective of this essay is to understand its forms  of economic organization and social  2 reproduction. The kinship was a key aspect in the e conomic management of the merchant  businesses, but also in the social joint of these f amilies. The social bonds that united to  these individuals were fundamental in their mobilit y and social reproduction. But also in  the processes of changes and permanence at the end  of the Old Regime.
Keywords: Family; merchant community; social reproduction; kinship; economic organization